(untitled) (Journal of Engineering, 2014)
In this paper the effect of engagement length, number of teeth, amount of applied load, wave propagation time, number of cycles, and initial crack length on the principal stress distribution, velocity of crack propagation, and cyclic crack growth rate in a spline coupling subjected to cyclic torsional impact have been investigated analytically and experimentally. It was found that the stresses induced due to cyclic impact loading are higher than the stresses induced due to impact loading with high percentage depends on the number of cycles and total loading time. Also increasing the engagement length and the number of teeth reduces the principal stresses (40%) and (25%) respectively for increasing the engagement length from (0.15 to 0.23) and the number of teeth from (8 to 10). while increasing the other parameters (amount of applied load, wave propagation time, number of cycles, and initial crack length) increase the principal stresses at the root of the tooth (37% when the applied load rises from (8 KN to 11KN) and (62% when the wave propagation time rises from (0.5 to 1).